2015
DOI: 10.1007/s11517-015-1423-3
|View full text |Cite
|
Sign up to set email alerts
|

Somnomat: a novel actuated bed to investigate the effect of vestibular stimulation

Abstract: Rocking movements are known to affect human sleep. Previous studies have demonstrated that the transition from wake to sleep can be facilitated by rocking movements, which might be related to relaxation. However, it is not yet known which movements would have the greatest effect. Thus, a 6-degree-of-freedom tendon-based robotic bed was developed, for systematic evaluation of vestibular stimuli. The applicability of the device was evaluated with 25 subjects. Six movement axes were tested and analyzed for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…More recently, healthy adult subjects rocked laterally during a single afternoon nap showed reduced sleep-onset latency, increased N2 duration, and enhanced electroencephalographic (EEG) markers of sleep quality [5]. Conversely, Omlin and colleagues, testing various planes of motion and rocking rates with a rhythmically moving bed, did not observe any influence of rocking on adult sleep [6,7]. Of note, rocking conditions, such as the duration, rate, and displacement, differed among the three studies.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, healthy adult subjects rocked laterally during a single afternoon nap showed reduced sleep-onset latency, increased N2 duration, and enhanced electroencephalographic (EEG) markers of sleep quality [5]. Conversely, Omlin and colleagues, testing various planes of motion and rocking rates with a rhythmically moving bed, did not observe any influence of rocking on adult sleep [6,7]. Of note, rocking conditions, such as the duration, rate, and displacement, differed among the three studies.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have suggested treatment approaches that include, for example, aversion or stimulus substitution approaches (5, 27, 28), which rely on a response to initiation of movement. For example, the Somnomat rocking bed, which formed part of this feasibility study (19), could be activated in response to the patient’s RMs.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected as part of a feasibility study () of sensory stimulation therapy in children with RMD (18, 19). Assessments were made in the University of Zurich, sleep laboratory, Switzerland.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, vestibular stimulation through swinging has demonstrated an accelerated effect in the wake/sleep transition and have highlighted sleep consolidation during napping Bayer et al 2011). Otolith stimulation induced by accelerated linear bed movements seems to have a potential effect on drowsiness (Woodward et al 1990;Crivelli et al 2016). Positive effects of vestibular stimulation on the wake/sleep transition were recently confirmed in mice (Kompotis et al 2019).…”
mentioning
confidence: 98%